1976
DOI: 10.1172/jci108467
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of lead metabolism in healthy humans.

Abstract: A B S T R A C T The steady state kinetics of lead metabolism were studied in five healthy men with stable isotope tracers. Subjects lived in a metabolic unit and ate constant low lead diets. Their intake was supplemented each day with 79-204 /Ag of enriched lead-204 as nitrate which was ingested with meals for 1-124 days. The concentration and isotopic composition of lead was determined serially in blood, urine, feces, and diet and less commonly in hair, nails, sweat, bone, and alimentary tract secretions by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
340
1
41

Year Published

1977
1977
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 648 publications
(392 citation statements)
references
References 14 publications
10
340
1
41
Order By: Relevance
“…On a comparative basis, Rabinowitz et al (33) point out that their results in humans differ from those reported for the rat and hamster. When rats and hamsters inhaled radioactive lead, lead accumulated in the erythrocytes only to about half the extent, there was more found in the kidneys, and clearance from the blood was more rapid (60).…”
Section: Environmental Health Perspectivesmentioning
confidence: 89%
See 3 more Smart Citations
“…On a comparative basis, Rabinowitz et al (33) point out that their results in humans differ from those reported for the rat and hamster. When rats and hamsters inhaled radioactive lead, lead accumulated in the erythrocytes only to about half the extent, there was more found in the kidneys, and clearance from the blood was more rapid (60).…”
Section: Environmental Health Perspectivesmentioning
confidence: 89%
“…However, its diagnostic value at the borderline of hazardous conditions is quite limited. It has been found that PbB is more a measure of very recent exposure (30)(31)(32)(33) than of total body burden, and most lead in the body is within the hard and soft tissues (33)(34)(35)(36). Below are some of the best data for "normal" concentrations of PbB.…”
Section: Terminologymentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma transfer of lead into bone, through partition exchange, results in the replacement of calcium within hydroxyapatite crystals by lead [9]. A three-compartment model of human lead metabolism and exchange developed by Rabinowitz et al illustrates the mean lifetime exposure of lead within soft tissue, blood, and bone [10]. Over time, bone serves as the largest volume for lead distribution with a total burden as high as 90-95% by adulthood [11].…”
Section: Introductionmentioning
confidence: 99%